MA’NAVIYAT – HUQUQIY DAVLAT TAYANCHI - Ergasheva, G.M. (SCIENCE and SOCIETY, 2024)
In this article, the issues of bringing this system to a higher level are studied, from highlighting the extremely important issue of attitude to democracy in our national spirituality in the formation of an active citizenship position in New Uzbekistan. The article also provides recommendations and conclusions regarding the development of an active civil society in our country by studying the spiritual and democratic legal issues in various countries where civil society is being established, studying their achievements and shortcomings.
Keywords: enlightened society; spirituality; rule of law; citizen activity; civil society; development strategy of new Uzbekistan